Optimization of Process Parameters of Abrasive Jet Machining on Hastelloy through Response Surface Methodology - Sreekanth, D. V.; Rao, M. Sreenivasa (Journal of the Institute of Engineering, 2018)
The demand for micro products is rapidly increasing in chemical, marine and aerospace industries. The super alloys which have high strength and corrosion resistance properties play a major role. Hastelloy which is difficult to machine by the conventional processes can be machined by using AJM. Hastelloy C276 sheet of thickness 1mm has been drilled on the AJM test rig using variable process parameters. In this paper optimization of process parameters of Abrasive Jet Machining of Hastelloy C276 by RSM methodology is presented. The values obtained in RSM Analysis were compared with the Analysis of Variance (ANOVA). Various levels of experiments are conducted using L15 orthogonal array for both MRR and KERF. Journal of the Institute of Engineering, 2018, 14(1): 170-178